Determinants of Voluntary Compliance on A Changing Tax Policy - Cahyonowati, Nur; Ratmono, Dwi; Dewayanto, Totok (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2023)
Purpose: This study aims to examine the effect of trust, power, procedural fairness, distributive fairness, tax morale, and tax complexity on voluntary compliance. This study is conducted in an environment where taxpayers have to adopt new practices in tax reporting.Method: This study applied a survey of staff and lecturers in one of the state universities in Semarang, Central Java. The questionnaires were distributed online. The final sample comprised 165 participants. The regression model will be analyzed using SmartPLS.Findings: The results suggested that procedural fairness, distributive fairness, and tax morale had a significant role to achieve voluntary compliance. However, this study failed to provide empirical evidence about the effect of trust, power, and tax complexity on voluntary compliance.Novelty: The dynamic at the organizational level has brought consequences for the members of the organization. The consequence includes a practical change in tax reporting i.e. from zero payment in tax returns to underpayment in tax returns. Under this background, this study investigates voluntary compliance and its determinants. The investigation is important since the practical changes in tax reporting tend to increase the tax burden, which could promote tax evasion.